2015
DOI: 10.1136/thoraxjnl-2015-207770.182
|View full text |Cite
|
Sign up to set email alerts
|

P45 Practical use of the DECAF score: Can we improve outcomes in acute exacerbation of COPD admissions?

Abstract: BackgroundAcute exacerbations of COPD (AECOPD) are the second most common cause of emergency hospital admission in England and are associated with an inpatient mortality rate of 4.3%.1 The Dyspnoea, Eosinopenia, Consolidation, Acidaemia and Atrial Fibrillation (DECAF) Score, is an effective prognostic tool that predict mortality in AECOPD admissions. This scoring system is easy to apply during admission and has performed better than existing prognostic tools.2 We aim to appraise the efficacy of DECAF score in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a comprehensive analysis of patients with AECOPD, the highest mortality was seen in patients with DECAF scores of 3-5 (92%). The in-hospital mortality rate increased with every point increase in the DECAF score [8]. In another study with an 18% mortality rate in patients with AECOPD, patients who died scored higher on both DECAF and the BAP-65 metric (B: elevated blood urea nitrogen, A: altered mental status, P: pulse >109, 65: age >65 years).…”
Section: Discussionmentioning
confidence: 91%
“…In a comprehensive analysis of patients with AECOPD, the highest mortality was seen in patients with DECAF scores of 3-5 (92%). The in-hospital mortality rate increased with every point increase in the DECAF score [8]. In another study with an 18% mortality rate in patients with AECOPD, patients who died scored higher on both DECAF and the BAP-65 metric (B: elevated blood urea nitrogen, A: altered mental status, P: pulse >109, 65: age >65 years).…”
Section: Discussionmentioning
confidence: 91%
“…The DECAF score has been further validated in external cohorts by subsequent studies, which have confirmed that DECAF is well-calibrated with excellent discrimination. 4,7,8 In 2018, a non-inferiority randomised controlled trial showed that low-risk (DECAF score 0-1) patients were suitable candidates for HAH treatment, with similar 90-day readmission and mortality rates between HAH and usual care groups. This protocol comprised nebulisation, intravenous antibiotics, steroids, temporary oxygen at home as well as telephone or in-person review by a respiratory clinical nurse specialist, if necessary.…”
Section: Decaf In the Literaturementioning
confidence: 99%